Review of the current wind energy technologies and global market - Komarov, Dragan; Stupar, Slobodan; Posteljnik, Zorana (Journal of Applied Engineering Science, 2011)
The modern wind energy technologies and recent global wind energy market trends are reviewed in the paper. Basic principles of conversion of wind energy to electricity are described with brief overview of the state-of-the-art technologies for subassemblies such as wind turbine blades and drivetrains. Global wind energy market was reviewed in order to attain notion of wind power market developments in the future. The most developed countries in terms of wind energy utilization such as Denmark, Germany, Spain and USA were identified as the key drivers of wind energy technology advances. After the long leadership of European Union in built annual wind power capacities, China and USA have overtook leading positions for the last several years. Wind energy costs per unit of electricity produced after gradual decrease until 2005 have recorded slight increase until the present due to high demand and higher raw materials price. It was predicted that the trend of the wind energy cost will decrease in the future. Steady growth of wind energy capacities was predicted in the next years, with forecast that present global installed capacities of nearly 200 GW should grow to almost one terawatt by the 2020.
Keywords: Wind turbine; Technology; Winds; wind energy; Markets; Globalization; energy use; capacity